GeoTPACK (Geographical Technology, Pedagogical, and Content Knowledge) Strategi Meningkatkan Keterampilan Geografi Berkelanjutan - Purwanto, Purwanto; Utomo, Dwiyono Hari; Wiwoho, Bagus Setiabudi; Susanto, Arif; Elvada, Erisa; Purba, Corrie Teresia; Zain, Moh Wahyu Kurniawan; Maghfiroh, Ainun; Mellyana, Iren Mega (Jurnal Pendidikan Geografi Undiksha, 2025)
The Geotpack (Geography Technology, Pedagogical, and Content Knowledge) Improvement Training for geography teachers in Situbondo Regency based on 3D Map Excel aims to overcome obstacles in the use of technology in geography learning. This training consists of three main stages: preparation, implementation, and evaluation and reflection. In the preparation stage, researchers identified the problem of low optimisation of technology use that hampers teachers' ability to teach spatial thinking concepts. The training then focused on the use of 3D Map Excel to visualize geographic data in three-dimensional form. During the training, participants were introduced to the TPACK concept that integrates technology, pedagogy and knowledge content. The practice of creating 3D maps was conducted using data from the Central Bureau of Statistics (BPS), with intensive mentoring to ensure the success of each participant. The evaluation results showed that all participants successfully applied the 3D map-making technique and planned to apply it in the classroom learning process. The implementation of 3D Map Excel technology is expected to increase the effectiveness of geography learning, create a more interactive and interesting atmosphere, and increase students' interest in learning. This training confirms the importance of improving teachers' competence in utilizing technology to create an innovative and effective learning environment.